Hormonal Regulation of Oligodendrogenesis II: Implications for Myelin Repair - Jocelyn M. Breton (Biomolecules, 2021)
Alterations in myelin, the protective and insulating sheath surrounding axons, affect brain function, as is evident in demyelinating diseases where the loss of myelin leads to cognitive and motor dysfunction. Recent evidence suggests that changes in myelination, including both hyper- and hypo-myelination, may also play a role in numerous neurological and psychiatric diseases. Protecting myelin and promoting remyelination is thus crucial for a wide range of disorders. Oligodendrocytes (OLs) are the cells that generate myelin, and oligodendrogenesis, the creation of new OLs, continues throughout life and is necessary for myelin plasticity and remyelination. Understanding the regulation of oligodendrogenesis and myelin plasticity within disease contexts is, therefore, critical for the development of novel therapeutic targets. In our companion manuscript, we review literature demonstrating that multiple hormone classes are involved in the regulation of oligodendrogenesis under physiological conditions. The majority of hormones enhance oligodendrogenesis, increasing oligodendrocyte precursor cell differentiation and inducing maturation and myelin production in OLs. Thus, hormonal treatments present a promising route to promote remyelination. Here, we review the literature on hormonal regulation of oligodendrogenesis within the context of disorders. We focus on steroid hormones, including glucocorticoids and sex hormones, peptide hormones such as insulin-like growth factor 1, and thyroid hormones. For each hormone, we describe whether they aid in OL survival, differentiation, or remyelination, and we discuss their mechanisms of action, if known. Several of these hormones have yielded promising results in both animal models and in human conditions; however, a better understanding of hormonal effects, interactions, and their mechanisms will ultimately lead to more targeted therapeutics for myelin repair.